Work Productivity Loss and Fatigue in Psoriatic Arthritis - Jessica A. Walsh; Molly McFadden; Michael D. Morgan; Allen D. Sawitzke; Kristina Callis Duffin; Gerald G. Krueger; Daniel O. Clegg (2014)
Objective. To explore the relationship between fatigue and work productivity loss (WPL) in people with psoriatic arthritis (PsA). Methods. Data were collected from participants in the Utah Psoriasis Initiative Arthritis registry between January 2010 and May 2013. WPL was measured with the 8-item Work Limitations Questionnaire. Fatigue was assessed with question 1 from the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI#1), “How would you describe the overall level of fatigue/tiredness you have experienced?” and with question 1 from the Psoriatic Arthritis Quality of Life Questionnaire (PsAQOL#1) “I feel tired whatever I do.” Psoriatic activity was evaluated with tender joint count (TJC), swollen joint count (SJC), dactylitis count, enthesitis count, inflammatory back pain (IBP), physician global assessment, body surface area, and psoriasis pain and itch. Results. Among 107 participants, work productivity was reduced by 6.7%, compared to benchmark employees without limitations. Fatigue was reported by 54 patients (50.5%) on PsAQOL#1, and 64 (60.0%) were classified as high fatigue by BASDAI#1. TJC, SJC, enthesitis count, IBP, and depressed mood were highest or most frequent in participants reporting fatigue. After adjustments for psoriatic activity and depressed mood, WPL was associated with fatigue, as measured by PsAQOL#1 (p = 0.01) and BASDAI#1 (p = 0.002). Conclusion. WPL was associated with fatigue, and the association was not entirely explained by the evaluated musculoskeletal, cutaneous, or psychiatric manifestations of PsA.